2008
DOI: 10.1007/s11515-008-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and characterization of man gene from Bacillus Subtilis in Pichia Pastoris

Abstract: b-Mannanase catalyzes endo-wise hydrolysis of the backbone of mannan and heteromannan, which are abundant in the cell wall structure of ungerminated leguminous seeds. The mature b-mannanase originated from Bacillus subtilis was expressed in Pichia pastoris, a methylotrophic yeast, using the leader peptide sequence of Saccharomyces cerevisiae a-factor. The cultivation of b-mannanase expressing Pichia pastoris yields up to 1.8 g/L protein. In the supernatant the activity of the 40 kDa-total mannanase attained a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
2
3
0
Order By: Relevance
“…The highest reported mannanase activity produced is 18,403 nkat ml -1 and was achieved by producing a B. subtilis mannanase in P. pastoris in a fermenter [4]. This compares favourably with the shake-flask-produced mannanase activity of 16,596 nkat ml -1 we report in this study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The highest reported mannanase activity produced is 18,403 nkat ml -1 and was achieved by producing a B. subtilis mannanase in P. pastoris in a fermenter [4]. This compares favourably with the shake-flask-produced mannanase activity of 16,596 nkat ml -1 we report in this study.…”
Section: Discussionsupporting
confidence: 67%
“…3.2.1.78) belongs to the glycosyl hydrolase family #5 and has been cloned from bacterial and fungal origins [1][2][3][4]. b-mannanases catalyse the random hydrolysis of the b-1, 4-mannan main chains of mannans and heteromannans.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained for an antifreeze protein expressed in P. pastoris when an induction temperature of 23°C was used [34]. Until now, only Zhu et al [35] reported that lowering temperature was beneficial to β‐mannanase production in P. pastoris , but they did not discuss it in detail. In this study, we proved that a two‐stage temperature control strategy was more efficient for β‐mannanase fermentation.…”
Section: Discussionsupporting
confidence: 63%
“…( 2001 ). Similarly, Qiao et al ( 2008 ) have used Pichia pastoris as a host for expression of MAN gene of Bacillus subtilis . It has been observed that, if the same gene encoding mannanase is expressed in different hosts, the resultant recombinant enzymes show somewhat different properties.…”
Section: Heterologous Productionmentioning
confidence: 99%